The Meaning and Adequacy of Alternative Sanctions - Nikolić, Zlatko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
The development of human relations that came with the development of civilization itself, has not led to the diminishing of criminal offences or penalties provided for them, which, as a consequence, led to rising of prison overcrowding. The consequences of imprisonment, and all of negative prison influences on convicts, however, lead to a thought that all offenders should not be punished through imprisonment, that it might be more useful or appropriate to use some kind of alternative to imprisoning or prisons. The following text is dedicated to a search for such alternatives, with a critical overview of past experiences.